2018
DOI: 10.1177/1534650118800809
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of a Commercially Sexually Abused Girl Using Trauma-Focused Cognitive Behavioral Therapy and Legal Interventions

Abstract: This case study describes the use of trauma-focused cognitive behavioral therapy (TF-CBT) and legal interventions for a 16-year-old girl who was the victim of commercial sexual exploitation (CSE) and suffered from substance abuse, anxiety, and body image issues. Over the course of 1 year, the client was able to discontinue involvement in sexual exploitation, cease substance use, decrease her anxiety level, improve her self-concept, and reduce posttrauma symptoms. The case calls attention to the need for extend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…For example, our participants did not all buy into traditional deep breathing techniques; thus, it was important to incorporate methods that were more helpful, such as square breathing and grounding techniques. Victims of sex trafficking are very dysregulated emotionally (Cohen et al., 2017; Kenny et al., 2019). Staying in a state of emotion dysregulation will often lead to more externalizing behaviors: being argumentative, fighting with peers and power struggles with staff along with suppression or avoidance to working on their trauma (Kenny et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, our participants did not all buy into traditional deep breathing techniques; thus, it was important to incorporate methods that were more helpful, such as square breathing and grounding techniques. Victims of sex trafficking are very dysregulated emotionally (Cohen et al., 2017; Kenny et al., 2019). Staying in a state of emotion dysregulation will often lead to more externalizing behaviors: being argumentative, fighting with peers and power struggles with staff along with suppression or avoidance to working on their trauma (Kenny et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Victims of sex trafficking are very dysregulated emotionally (Cohen et al., 2017; Kenny et al., 2019). Staying in a state of emotion dysregulation will often lead to more externalizing behaviors: being argumentative, fighting with peers and power struggles with staff along with suppression or avoidance to working on their trauma (Kenny et al., 2019). Understanding what will help DMST victims take interest and use emotion regulation and relaxation skills within their environment is a significant focus of TF‐CBT in preparation for working through cognitive distortions and memories of their trauma (Cohen et al., 2017; Kenny et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These skills likely far exceed those of other professionals, such as law enforcement, who may have more limited training and exposure engaging youth in conversations beyond interrogations and witness questioning. On the other hand, however, it is not clear that school professionals have received training in or are knowledgeable about effective rapport building or interview strategies known to elicit disclosures of abuse or other forms of victimization (Hershkowitz & Lamb, 2020;Karni-Visel et al, 2019, 2021Saywitz et al, 2019), or about open-ended prompting, which has been widely shown to elicit complete disclosures of abuse from victims and witnesses spanning childhood through early adulthood (Ahern et al, 2017(Ahern et al, , 2019Cleary, 2017;Kenny et al, 2019;Simpson et al, 2023). Adolescents, like children and adults can be led to error when asked closed-ended and possibly leading questions (Leach et al, 2017), including from well-intentioned and supportive 1 It should be noted that sexual exploitation of minors and sex trafficking of minor overlap some but are not synonymous (Institute of Medicine & National Research Council, 2013).…”
Section: Practitioner Pointsmentioning
confidence: 99%